Die Emanzipation de Frauenbildes : eine Untersuchung der Rolle des Goetheschen Romans "Die Wahlverwandtschaften" in Maja Beutlers Konzept der "Wortfalle": a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts at Massey University - Palmboom, Sigrid (Massey University, 1996)
In this thesis, Maja Beutler's novel, "Die Wortfalle", ("The Wordtrap"), is compared with Goethe's novel, "Die Wahlverwandtschaften" ("The Elective Affinities"), with the purpose of ascertaining why Maja Beutler uses themes, the name of the main character and direct quotations from Goethe's novel in her own work. Maja Beutler recalls the older novel (published in 1809) in order to confront the male perspective, from which Goethe presents the world and human-relations, with the more modern perspective of a woman, and to offer a solution to the present-day alienation and dehumanisation, that has resulted from the disintegration of the total world-view, which characterized the German Classical Age. Goethe's novel, "Die Wahlverwandschaften" (1809), illustrates the beginning of the disintegration process, whereby the components of the whole, i.e. the metaphysical sphere, the physical sphere and the word (the expression of the true perception of the unified whole) were no longer interdependent but became autonomous. The main male character, Eduard, is dominated by his physical drives, i.e. his sensuous passion for his wife's niece, Ottilie, to the exclusion of his powers of reasoning and moral discernment. The word, in his mouth, divorced from factual reality and reasoned perception of the truth, serves his sensuous passion and becomes a "word-trap", which determines his perception and manipulates Ottilie's perception. This leads to the tragedy, the accidental death of Eduard's and his wife's child in Ottilie's care, which causes her to realise that she has allowed herself to fall into the grip of demonic forces. She attempts to regain her inner integrity by renouncing Eduard, but when this is thwarted by a freak stroke of chance, she realises that the demonic forces had not only taken hold on her, but also on the outside world. In resolving to renounce her physical existence altogether, to sacrifice herself to atone for the evil she had helped to release in the world, she reaches the heights of "absolute love" and is sanctified in death. Maja Beutler has written a sequel to Goethe's novel, in which she shows that "absolute love", a spiritual love, as opposed to Eduard's sensuous passion, is the basis of a true perception of the world and human-relations - a concept akin to Martin Buber's I/Thou relationship - which in turn is the basis for restoring the word to its original creative function of serving the expression of true perception rather than creating a false image and obscuring true perception. Maja Beutler's main male character, Gandolfi, a psychiatrist, is caught in the "word-trap" of his profession, which determines his false image of reality, human-relationships and in particular of his wife, Otti. His false perception, imposed by the "word-trap", illustrates the extent of the fragmentation of the whole: he fails to perceive the complementary unity between male and female, and he divides the woman into two further categories: "femme fatale" and "femme fragile". By introducing Kafka's "Verwandlung" (Metamorphosis) as one of the main motifs, Maja Beutler points to the alienation and dehumanisation that this false perception has brought about. She also uses Kafka's title to point to her main female characters attempt, Otti's, to reverse the process and change the dehumanized human-being back into human form by breaking down the false images and enabling the male to experience "absolute love" and true perception. The initiative must be taken by the woman, who must first enter the male world of thinking before she can save him from his own word-trap. The concept of the complementary unity between the disparate parts of the whole is illustrated by the image of the butterfly, with the mirror-image of its wings. This is the symbol, upon which the structure of the novel is based.
Abstract in English - text in German
Keywords: Beutler, Maja, 1936-; Goethe, Johann Wolfgang von, 1749-1832